Magnetic Resonance Enterography Findings in Crohn′s disease in the Pediatric Population and Correlation with Fluoroscopic and Multidetector Computed Tomographic Techniques - Patel, Parul (Medknow Publications & Media Pvt Ltd, 2011)
Traditionally, fluoroscopic examinations such as enteroclysis, upper GI studies, and small bowel follow through exams have been the procedures of choice in evaluating inflammatory bowel disease (IBD) in pediatric populations. With the advent of multidetector computed tomography (MDCT), it has subsequently become a complementary examination in imaging inflammatory bowel disease. A major advantage of MDCT over fluoroscopic examination is its ability to directly visualize bowel mucosa, as well as demonstrate extra-enteric complications of IBD such as abscesses, fistulae, and sinus tracts. The major disadvantage of CT however is exposure to ionizing radiation, especially in IBD patients of the pediatric age group who maybe repeatedly imaged due to exacerbations. As a result, magnetic resonance enterography (MRE) is becoming increasingly important in the evaluation and follow-up of pediatric patients with IBD. This pictorial essay will summarize the multi-modality imaging findings of IBD with emphasis on MRE including the imaging protocol and procedure. For the purposes of this article, patients less than 17 years of age have been considered to represent the pediatric population.